Cooperative learning: Addressing implementation issues - Willy A. Renandya; George M. Jacobs (Universitas Katolik Indonesia Atma Jaya, 2017)
Although cooperative learning (CL) has been shown to be an effective method to increase students’ levels of engagement in the language classroom, not all teachers use it regularly. Some may not fully understand its theoretical rationales, some may not be aware of its potential language learning benefits and some may just feel that CL takes up too much of instruction time. In this paper, we first provide the key theoretical principles behind CL and discuss four such principles that research has shown to be essential. These are positive interdependence, maximum peer interactions, equal opportunity to participate and individual accountability. In the last part, which forms that bulk of this paper, we discuss common concerns teachers have about CL and offer practical suggestions of addressing them.